STUDI LITERATUR: ACUPRESSURE PERICARDIUM DAN AROMATHERAPY CITRUS UNTUK MENGURANGI MUAL MUNTAH IBU HAMIL - Uning Sulistiarini; Melyana Nurul Widyawati; Dyah Lustika Rahayu (JURNAL KEBIDANAN, 2018)
Changes during pregnancy that make discomfort require an adaptation process. Nausea and vomiting discomfort can occur in 60-80% of primigravida pregnancies and 40-60% of multigravida pregnancies. Symptoms of nausea can be severe if not managed properly. Various efforts have been made to reduce maternal nausea and vomiting. In addition to pharmacological therapy can also be carried out nonphamacological therapy that is simple, inexpensive, effective, and without adverse side effects, namely in the form of acupressure or massage at the point 6 of the pericardium and administration of aromatherapy.The aim of the study was to measure literature related to pericardium acupressure and citrus aromatherapy. Methods: the method used is a literature study on the effectiveness of pericardium acupressure and citrus aromatherapy for pregnancy. The source of literature uses electronic media with various journals and libraries in 2008-2018 from several databases, namely Sience Direct and Google Scholar.The article found as many as 5 journals consisting of 2 international journals and 3 national journals. Research design: descriptive design, by analyzing journals related to the topic. Results: the results of the literature review were complementary follow-up treatment of pericardium P6 acupressure and citrus aromatherapy categorized as safe and effective enough to reduce nausea and vomiting in pregnancy. The conclusions from this literature review that the of pericardium P6 acupressure and citrus aromatherapy administration showed its effectiveness in combining nausea and vomiting in pregnancy.